The effects of mode of delivery on Mutans Streptococci colonization and dental caries in a sample of Iraqi children aged 3-5 years from Baghdad city (Mustansiria Dental Journal, 2018)
Aim: To investigate whether mode of delivery is associated with mutans streptococci(MS) colonization and dental caries in pre school children.Methods: This study includes 64 pairs of mothers and their children aged 3- 5 yearsold (34 born vaginally and 30 born by Caesarean section).Data included a dentalexamination, a questionnaire survey of mode of delivery, maternal gestationalage, as well as children's birth –weight, and laboratory assessment (by collectingnon stimulated saliva for each woman and child and homogenizing them thenMutans Streptococci (MS) were counted ,isolated, purified and diagnosedaccording to morphological characteristic .Results: Dental caries, salivary and plaque streptococcus mutans counts weresignificantly higher in children delivered by caesarean section mode than thosedelivered normally (P